Determinants of Carbon Emission Disclosure with Media Exposure as a Moderator - Desak Nyoman Sri Werastuti; Anantawikrama Tungga Atmadja; I Made Pradana Adiputra (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
Main Objectives: The purpose of this study is to investigate the effect of environmental performance, good corporate governance, and company size on carbon emission disclosure, with media exposure as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2025 period. Methods: The research approach is quantitative, supported by panel data regression analysis using Moderated Regression Analysis (MRA) and the selected model is the random effects model (REM). The sample size was 42, with 210 observations, and data processing was carried out using Eviews 13. Results / Findings: The study's findings indicate that environmental performance, the board of commissioners, and the board of directors have no significant effect on emission disclosure, while company size has a positive and significant effect on carbon emission disclosure. Conclusion: Furthermore, media exposure does not moderate the effects of environmental performance, the board of commissioners, the board of directors, and company size on carbon emission disclosure.